2004
DOI: 10.1111/j.1442-200x.2004.01881.x
|View full text |Cite
|
Sign up to set email alerts
|

Population attributable fraction of smoking to low birth weight in Japan

Abstract: Public education to eliminate passive smoking for pregnant women and smoking prevention in adolescence is very important in order to reduce the risk of low birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 10 publications
3
15
0
Order By: Relevance
“…26 There was evidence of the number-related effect of active and passive smoking on birthweight. Ojima et al 27 also reported that passive smoking at home among expectant mothers presented a 1.3 times greater risk of having a LBW infant than when there are no smokers in the workplace or at home. The birthweight of babies in women smoking between 1 and 14 cigarettes per day was 140 g lighter after adjustment for gestational age, maternal height (160 cm), infant sex, and parity, but not for maternal weight gain, than those infants born to non-smokers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…26 There was evidence of the number-related effect of active and passive smoking on birthweight. Ojima et al 27 also reported that passive smoking at home among expectant mothers presented a 1.3 times greater risk of having a LBW infant than when there are no smokers in the workplace or at home. The birthweight of babies in women smoking between 1 and 14 cigarettes per day was 140 g lighter after adjustment for gestational age, maternal height (160 cm), infant sex, and parity, but not for maternal weight gain, than those infants born to non-smokers.…”
Section: Discussionmentioning
confidence: 98%
“…7,8 In Japan, a decline in BMI has been observed in all age groups. The incidence of low bodyweight has increased from 19.6% in 1986 to 21.7% in 2006 among [20][21][22][23][24][25][26][27][28][29] year olds, and from 8.6% to 13.3% among 30-39 year olds. 9 A low BMI in highly industrialized countries cannot be considered to be a result of environmental factors such as periodic food shortages and malnutrition, but as an expression of constitutional low weight or a result of cosmetically-induced starvation.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the analysis carried out using model 1 that suggested maternal smoking during pregnancy and maternal lower BMI before pregnancy were risk factors of LBW were in agreement with the results of previous reports. [5][6][7][8][9][10] Second, by using model 2, we examined the relationship between maternal attitudes during pregnancy and LBW. The results of the analysis carried out by using model 2 revealed that maternal negative attitudes towards pregnancy promoted the incidence of LBW.…”
Section: Discussionmentioning
confidence: 99%
“…4 LBW is generally associated with conditions wherein altered placental circulation leads to intrauterine malnutrition. 5 There are several known risk factors for the above-mentioned condition, and the most important factors are maternal smoking before or during pregnancy, [5][6][7][8][9] maternal body mass index (BMI) before pregnancy, 5,6,10-12 maternal weight gain during pregnancy, 10,11 working during pregnancy (including housekeeping activities) 5,[13][14][15] and maternal psychological status. 5,7,[15][16][17][18] With regard to the correlation between LBW and maternal stress, well-controlled research has documented that high levels of maternal anxiety and depression result in reduced birth weight and a smaller head size (a measure of brain development).…”
Section: Introductionmentioning
confidence: 99%
“…In that study, maternal smoking during pregnancy accounted for 22% (15-29%) of all LBW babies in the population, 14% (10-18%) of SGA babies, and 7% (1-12%) of preterm babies. Ojima et al (2004) reported on the population-attributable proportion of active and passive smoking for LBW. These results showed the population-attributable proportion of smoking among mothers without preeclampsia during pregnancy was 7.0% for active smoking and 15.6% for passive smoking.…”
Section: Disease Burden From Air Pollution and Smokingmentioning
confidence: 99%